Development and validation of the job stressor scale for specialty nurses - Zhang, Panpan; Lin, Wenqiong; Li, Songyao; Li, Yaru; Wei, Jili; Zhang, Huiyi; Zhang, Bo; Fang, Ziru; Guo, Rui; Zhang, Hongmei (Frontiers in Psychology, 2024)
Objectives Specialty nurses play a crucial role in specialized nursing practice, teaching, management, and research. These nurses often face significant work pressure; therefore, scientifically and effectively assessing their job stress and its sources is vital for enhancing the quality of their work. However, there is currently a dearth of verified assessment tools for measuring job stressors among specialty nurses. Therefore, this study aimed to develop and test an instrument to assess the job stressors applicable to specialty nurses. Methods We conducted a multiphase mixed-methods study. The initial scale items were developed from a literature review and structured interviews. The scale was then refined through two rounds of expert consultation (N = 14) and a primary test (N = 20). A main survey (N = 552) was then conducted to evaluate the scale’s construct validity and reliability using confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). Results The final scale comprises four dimensions with 27 items. The factors included “specialized nursing and work,” “workload and time allocation,” “patient care,” and “work resources and environment.” The EFA explained 69.10% of the variance, while the CFA confirmed a good model fit. The content validity index was 0.980 at the scale level and 0.790–1.000 at the item level. The scale’s reliability was supported by its high Cronbach’s α (0.958), test–retest reliability (0.946), and split-half reliability (0.868). Conclusion Our findings indicate that the job stressor scale developed in this study is valid and reliable, and is recommended for use among specialty nurses to assess their stressors.